Generic Review of New Zealand Chrysomelinae (Coleoptera: Chrysomelidae) - Leschen, Richard A.b.; Reid, Chris A. M.; Nadein, Konstantin S. (Zootaxa, 2020)
The leaf beetle subfamily Chrysomelinae is reviewed for New Zealand. The native fauna consists of six genera, three new, all of which are described: Aphilon Sharp, 1876; Caccomolpus Sharp, 1886; Chalcolampra Blanchard, 1853; Mauroda gen. nov.; Nanomela gen. nov.; Zeaphilon gen. nov.. Chalcolampra is the senior synonym of Cyrtonogetus Broun, 1915 (comb. nov.). These genera include 51 species, nine newly described and eight in new combinations, as follows: Caccomolpus laticollis (Broun, 1893) comb. nov., from Aphilon; C. pretiosus (Broun, 1880) comb. nov., from Aphilon; Chalcolampra crassa (Broun, 1915) comb. nov., from Cyrtonogetus; Maurodus arcus sp. nov.; M. cinctiger (Broun, 1921) comb. nov., from Caccomolpus; M. impressus (Broun, 1914) comb. nov., from Aphilon; M. lepidus sp. nov.; M. maculatus (Broun, 1893) comb. nov., from Caccomolpus; M. nunni sp. nov.; M. occiduus sp. nov.; M. ornatus (Broun, 1910) comb. nov., from Caccomolpus; M. owenensis sp. nov.; M. plagiatus (Sharp, 1886) comb. nov., from Caccomolpus; M. supernus sp. nov.; Nanomela tiniheke sp. nov.; Zeaphilon marskeae sp. nov.; Z. mirandum sp. nov.. All 11 species in the genus Maurodus are described and a key given for their identification. Type material of the New Zealand species of Aphilon (10 species), Caccomolpus (14 species) and Chalcolampra (13 species) is reviewed and lectotypes designated for 16 species, as well as M. cinctiger. A type species is designated for Caccomolpus: C. globosus Sharp, 1886. Holotypes are confirmed for 26 species. Seven genera and 13 species of exotic Chrysomelinae also occur in New Zealand and their presence is briefly reviewed. One of these exotics has been misnamed as Paropsisterna variicollis (Chapuis, 1877), a junior synonym of P. cloelia (Stål, 1860) (syn. nov.). A key to all genera of Chrysomelinae in New Zealand is provided.